Gray matter volume microstructural alterations in chronic post-burn pruritus: a voxel-based morphometry analysis using 3D T1-weighted imaging - Lu, Zhi-kai; Li, Xiao-yan; Huang, Yin; Guo, Wan-li; Bai, Pei-yi; Liu, Lu; Zhu, Jin-feng; Wang, Rui (Frontiers in Neuroscience, 2025)
BackgroundChronic post-burn pruritus (CPBP) refers to a highly prevalent as well as debilitating problem after burn injuries, substantially impairing patients’ quality of life. Nevertheless, the precise pathological mechanisms underlying CPBP remain elusive. The present study seeks to investigate microstructural changes in gray matter among individuals with CPBP and to evaluate associations between these changes and clinical scale scores via voxel-based morphometry (VBM).Materials and methodsWe recruited 20 people having CPBP and 20 healthy controls (HCs) who were of the same sex and age. T1-weighted imaging in three dimensions (3D-T1WI) was performed on each participant. Using VBM, volumes of gray matter in each region were measured. Volume differences between groups were measured, and it was methodically examined how the volume in particular brain regions correlated with clinical markers.ResultsWe found no discernible age difference between the groups (P > 0.05). Compared with HCs, patients with CPBP showed reduced gray matter volume across multiple brain regions (P < 0.05). These regions encompassed the bilateral parahippocampal gyri, right medial frontal gyrus, right middle frontal gyrus, left cerebellum posterior lobe, left fusiform gyrus, left superior occipital gyrus, left middle temporal gyrus, left cuneus, inferior parietal lobule, right medial frontal gyrus, and left superior temporal gyrus. Furthermore, correlation analysis showed a negative relationship between the individuals’ Self-Rating Depression Scale scores and the gray matter volume in the right superior temporal gyrus in patients with CPBP (r = −0.632, P = 0.003).ConclusionThe frontal, temporal, parietal, occipital, and cerebellar regions all exhibit a marked reduction in volume in response to CPBP.